Sensitivity Analysis of Copolar Complex Coherence for Crop Monitoring At L-Band - Jiayin Luo; Juan M. Lopez-Sanchez; Irena Hajnsek (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Time series of polarimetric synthetic aperture radar (SAR) images are usually employed for agricultural crop monitoring. Most methods exploit backscattering coefficients, radar vegetation indices (RVI), and outputs from target decompositions. This article investigates the sensitivity of the copolar complex coherence to the growth of three crop types (barley, corn, and canola) using L-band data from two airborne campaigns. The copolar complex coherence is represented on the complex plane (unit circle) for interpretation. The experimental results from this article reveal that the changes in the position of the copolar complex coherence and the shape of complex coherence region are highly sensitive to specific growth stages of the examined crops. For a given crop type, changes in coherence can reflect variations in crop biophysical parameters, and inhomogeneities within the field. Furthermore, the trends in coherence variation throughout the given growth stages differ among crop types.